(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Government of India launched Digital India to provide high-speed internet networks to rural areas. Digital India was founded with the goal of achieving inclusive growth in electronic services, goods, manufacturing, and job prospects. Due to this digital vision, digital payments have emerged as a popular and convenient method of paying for goods and services. Transactions made over the internet or through other electronic channels are known as digital payments .With more and more people opting for cashless transactions, digital payments have become an increasingly important part of the global economy. So the study focus on impact of digitalization on rural people intention to use digital payments systems with the objectives of factors impacting adoption of digital payments, problems confronting on usage of digital payments. The study also made an attempt to study the awareness level of rural people regarding digital payments along with how rural people perceive digital payment systems for digital transactions. Primary data collected through interview schedule are analysed using percentage analysis, descriptive analysis and ranking are made through weighted score and garret ranking method. For testing hypothesis of the study Freidman test, independent sample t test, chi square test and one-way ANOVA are employed.